Classification of mild cognitive impairment and dementia in alzheimer’s disease using spatio-temporal convolutional neural network (cnn) method - Turhan, Gülce (My University, 2020)
Makine öğrenmesi metodları gelişimi, son zamanlarda Alzheimer Hastalığı tanısının erken teşhişinde belirgin şekilde hızlanmıştır. Bu çalışmada; manyetik rezonans görüntüleri (MRI) üzerinden Alzheimer hastalığını (AD) hafif kognitif bozukluktan (MCI) ayırmak için bir (2+1) boyutlu evrişimsel sinir ağları yapısı önerilmiştir. AD ve MCI görüntüleri Alzheimer’s Disease Neuroimaging Initiative (ADNI) veritabanından alınmıştır. Bilgisayarlı deneylerde 223 Alzheimer hastasından alınmış 526 görüntü ve 204 hafif kognitif bozukluk hastasından alınmış 526 görüntü kullanılmıştır. Bu çalışmada; 2 boyutlu, 3 boyutlu ve (2+1) boyutlu evrişimsel sinir ağları modellerinin sonuçları ve hızları karşılaştırılmıştır. Evrişimsel sinir ağları algoritması mimariye bağlı olarak, 16 ilâ 24 evrişimsel sinir katmanı, ardından 4 ortaklama katmanı ve 3 tam bağlantılı katman gelecek şekilde birleştirmiştir. (2+1) boyutlu evrişimsel sinir ağı modeli, 0.94 doğruluk oranıyla en iyi sınıflandırmaı performansını göstermiştir. Buna ek olarak, klasik 3 boyutlu modellerle kıyaslandığında 2 kat daha hızlı çalışmıştır.

Development of machine learning algorithms have recently gained a significant pace in early diagnosis of Alzheimer’s disease (AD). In this study, a (2+1)D convolutional neural network (CNN) architecture has been proposed to distinguish AD from mild cognitive impairment (MCI) based on structural magnetic resonance imaging (MRI). MRI scans of AD and MCI subjects were procured from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) database. 526 scans of 223 AD patients and 526 scans of 204 MCI patients were obtained for the computational experiments. In this study, the outcome and robustness of 2D convolutions, 3D convolutions and (2+1)D convolutions were compared. The CNN algorithms incorporated 16 to 24 convolutional layers, depending on the architecture, followed by 4 pooling layers and 3 fully connected layers. (2+1)D convolutional neural network model resulted in the best classification performance with 0.24 test loss and 0.94 accuracy rates, in addition to an almost two times faster convergence compared to classical 3D CNN methods.
Keywords: Alzheimer Hastalığı; Convolutional Neural Network; Electric engineering; Electronics engineering; Elektrik mühendisliği; Elektronik mühendisliği; Evrişimli Sinir Ağları Alzheimer's Disease